Tardigrades of the Australian Antarctic: Hypsibius heardensis (Eutardigrada: Hypsibiidae: dujardini group) a new species from sub-Antarctic Heard Island - Miller, William R.; Mcinnes, Sandra J.; Bergstrom, Dana M. (Zootaxa, 2005)
A new species, Hypsibius heardensis sp. nov. (Tardigrada: Eutardigrada: Hypsibiidae) is described from samples collected during the Australian National Antarctic Research Expeditions (ANARE) 1986-87 expedition to Heard Island, in the southern Indian Ocean. The new species belongs to the dujardini group and differs from similar species of Hypsibius by the absence of eyes, large apophyses, near equal macroplacoids, lack of a microplacoid, the presence of a small septulum, and cuticular bars near the base of all claws.